Maternal folic acid supplementation to prevent preeclampsia: a systematic review and meta-analysis - Huaixing Cui; Naijin Zhang; JiaLi An; Xianyue Zeng; Ye Zhao; Xuan Sun; Huaien Bu; Hongwu Wang (Elsevier, 2024)
Objective: The purpose of this systematic review was to examine the association between folic acid supplementation during pregnancy and the risk of preeclampsia. Methods: Relevant studies were included by searching Embase, PubMed, Scope, Web of science, Cochrane Library databases. Studies were reviewed according to prespecified inclusion and exclusion criteria. Study characteristics were summarized, and study quality was assessed. Risk ratios (RR) and 95% confidence intervals (CI) were used as indicators of effect to assess the relationship between folic acid supplementation and risk of preeclampsia. Results: The protocol of this study was prospectively registered with the PROSPERO (registration No. CRD42022380636). A total of nine studies were included, divided into three groups according to the type of study, containing a total of 107 051 and 105 222 women who were supplemented and not supplemented with folic acid during pregnancy. The results showed that folic acid supplementation during pregnancy could not be proven to reduce the risk of preeclampsia. Conclusion: The results of the study suggest that folic acid supplementation alone is not associated with a decreased risk of pre-eclampsia,but the inferences are somewhat limited by the low methodological quality of the included literature, and therefore higher quality studies are needed to prove this point.